Effect of Flasking and Polymerization Techniques on Tooth Movement in Complete Denture Processing - Shibayama, Ricardo; Gennari Filho, Humberto [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Vedovatto, Eduardo; Assunção, Wirley Goncalves [UNESP] (Wiley-Blackwell, 2009)
Purpose: The purpose of this study was to compare the artificial tooth positional changes following the flasking and polymerization of complete dentures by a combination of two flasking methods and two polymerization techniques using computer graphic measurements.Materials and Methods: Four groups of waxed complete dentures (n = 10) were invested and polymerized using the following techniques: (1) adding a second investment layer of gypsum and conventional water bath polymerization (Control), (2) adding a second investment layer of gypsum and polymerization with microwave energy (Gyp-micro), (3) adding a second investment layer of silicone (Zetalabor) and conventional polymerization (Silwater), and (4) adding a second investment layer of silicone and polymerization with microwave energy (Silmicro). For each specimen, six segments of interdental distances (A to F) were measured to determine the artificial tooth positions in the waxed and polymerized stages using software program AutoCad R14. The mean values of the changes were statistically compared by univariate ANOVA with Tukey post-hoc test at 5% significance.Results: There were no significant differences among the four groups, except for segment D of the Silmicro group (-0.004 +/- 0.032 cm) in relation to the Gypwater group (0.044 +/- 0.031 cm) (p < 0.05), which presented, repectively, expansion and shrinkage after polymerization.Conclusions: Within the limitations of this study, it was concluded that although the differences were not statistically significant, the use of a silicone investment layer when flasking complete dentures resulted in the least positional changes of the artificial teeth regardless of the polymerization technique.
Keywords: Maxillary complete denture; acrylic resins; microwave; silicone; artificial tooth